2015
DOI: 10.1590/0103-9016-2014-0003
|View full text |Cite
|
Sign up to set email alerts
|

Water extraction variability in the banana root zone affects the reliability of water balance

Abstract: Spatial and temporal variability of soil water extraction from the root zone affect soil water balance determination. The number of sensors installed in the root zone in studies addressing water balance is still set arbitrarily. This study provided an investigation of the water extraction process by banana (Musa spp.) roots by (i) determining the variability of water extraction from the banana tree root zone, (ii) detecting differences in the estimation of evapotranspiration (ET) by the soil water balance meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 18 publications
(20 reference statements)
1
11
0
1
Order By: Relevance
“…The only exception was observed in the vegetative growth stage, in one of the four soil profiles, and only for depths z = 0.1 m and z = 0.5 m, where the highest mean deviations were also observed (Figure 2A). This fact should be related to a higher growth rate of banana roots at this stage (Silva et al, 2015). roots (Steudle and Frensch, 1996;Barrowclough et al, 2000;Watt et al, 2008;Draye et al, 2010).…”
Section: Definition Of the Effective Water Extraction Zones For The Bmentioning
confidence: 93%
See 2 more Smart Citations
“…The only exception was observed in the vegetative growth stage, in one of the four soil profiles, and only for depths z = 0.1 m and z = 0.5 m, where the highest mean deviations were also observed (Figure 2A). This fact should be related to a higher growth rate of banana roots at this stage (Silva et al, 2015). roots (Steudle and Frensch, 1996;Barrowclough et al, 2000;Watt et al, 2008;Draye et al, 2010).…”
Section: Definition Of the Effective Water Extraction Zones For The Bmentioning
confidence: 93%
“…The data were obtained from the same experiment in study of Silva et al (2015). Thus, edaphoclimatic conditions, lysimeter installation and assembly, construction and installation of TDR probes, soil water content monitoring, irrigation system and management, planting and cultivation practices of the banana crop, and experimental period are the same as those used in the study previously mentioned.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed understanding on the spatial-temporal variation of soil water storage in the root zone of crops can promote recommendations, as well as the effective root depth for water uptake, promoting accuracy in the irrigation depth calculation (Silva et al 2015;Silva et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown the existence of variability of water extraction in the root zone of various crops (JAVAUX et al, 2008;COELHO FILHO, 2009;SRAYEDDIN;DOUSSAN, 2009;DABACH;SHANI;LAZAROVITCH, 2016). In a study with the banana crop Silva, Coelho and Coelho Filho (2015) observed that spatial variability of water extraction (WE) affects the crop evapotranspiration (ET) estimate through SWB. However, in the case of short-cycle crops it is still a hypothesis the claim that the WE variability can affect the precision and accuracy of the ET estimates by SWB.…”
Section: Introductionmentioning
confidence: 99%